Influence of Maneuvering Singa Feeder at Bukit Siguntang Substation on Power Shrinkage Using ETAP 19.0.1 - Anton Firmansyah; Destra Andika Pratama; M. Raihan Ismail (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2022)
The need for electricity supply in the community and industry is increasing over time, it is necessary to provide energy and a safe and reliable electricity distribution system, which can minimize blackouts so as to maintain customer satisfaction. One way to increase reliability and minimize blackouts is through a network maneuvering process. This study calculates the magnitude of the power loss value on the power line in the feeder that maneuvers the Singa feeder with the aim of knowing the value of power loss that occurs during the maneuver so that network maneuvering activities on the Singa feeder become more optimal. The Singa feeder can be maneuvered by two feeders, namely the Kijang feeder and the Kancil feeder. Based on SPLN 72: 1987, the standard maximum value for medium-voltage